Severe thrombocytopenia as a presentation of thyrotoxicosis due to Graves-Basedow disease in a pregnant patient. Case report - Solano-Patiño, Lenin Gonzalo (2025)
Introduction: Graves-Basedow's disease is an autoimmune entity, which in pregnancy has a low prevalence, whose clinical manifestations are secondary to thyrotoxicosis and in rare cases may have hematologic manifestations. Objective: To describe the case of a pregnant woman with severe thrombocytopenia secondary to Graves-Basedow disease, its treatment during pregnancy and the clinical evolution of the mother-child binomial. Case presentation: It is shown the clinical case of a 22-year-old female patient, 7 weeks pregnant, who presented vomiting up to 30 times a day, for 2 weeks, with self-limited episodes of epistaxis. She was diagnosed with thyrotoxicosis due to Graves' Basedow disease, associated with severe thrombocytopenia. Treatment included corticosteroids, antithyroid drugs, beta-blockers and immunomodulators. Discussion: The association of severe thrombocytopenia and Graves' Basedow disease is uncommon, its diagnosis during pregnancy is a clinical challenge, since it is necessary to rule out other gestational disorders. Therapeutic options in the first trimester of pregnancy are limited by the increased risk of teratogenicity. Conclusions: The correct and timely diagnosis of this disease, allowed pharmacological decisions to be made in accordance with gestational age, thus achieving a pregnancy at term without complications.